Figure of A. Richynsky in modern Ukrainian religious studies - Shamadylo, Iryna (Ukrai͏̈ns'ke relihijeznavstvo, 2014)
The article of Shmadylo I. «Figure of A. Richynsky in modern Ukrainian religious studies» examines the state of sources and Ukrainian historiography related to the study of theoretical heritage, socio-political and religious activities of A. Richynsky.